Dynamic leadership models for global business : enhancing digitally connected environments - Smith, Peter A. C., 1933-; Cockburn, Tom, 1969- (Hershey, PA : Business Science Reference, 2013)
'This book describes various models on how to become an outstanding leader in today's rapidly growing global business environment, providing positive instruction that illuminates a practical path to becoming a successful leader in large and competitive markets'--Provided by publisher.
'Premier reference source'--Cover.
Includes bibliographical references and index.
Keywords: Leadership; Management; Information technology -- Management; Technological innovations -- Management